Leveraging Psychological Capital as a Personal Resource to Enhance Happiness at Work and Drive Extra-Role Behaviors - Iis Istiqomah; Yasmine Nasution (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study examines the effect of psychological capital (PsyCap) on happiness at work (HAW) and organizational citizenship behavior (OCB), while exploring the mediating role of HAW. Using data from 1,236 employees of a public financial organization in Indonesia, this research applied confirmatory factor analysis (CFA) and covariance-based structural equation modeling (CB-SEM). The results show that PsyCap significantly enhances OCB, both directly and indirectly through HAW. These findings highlight the critical role of emotional well-being as a psychological pathway that connects personal resources to positive work behavior. By adopting the Broaden-and-Build Theory, this study provides new insights into the mechanisms that promote extra-role behaviors in the workplace, particularly in public sector organizations. It also emphasizes the practical importance of developing PsyCap and fostering happiness at work to support organizational success.